The numerical solution of the one-dimensional heat equation by using third degree B-spline functions - Çağlar, Hikmet; Özer, Mehmet; Çağlar, Nazan (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2008)
In this paper, the boundary value problem for the one-dimensional heat equation with a nonlocal initial condition is examined by using the third degree B-splines functions. The numerical solution of the equations are discussed and illustrated with an example. The results of numerical testing show that the numerical method based on the given techniques produce good results. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: boundary-value-problems; Sınır-değer-problemleri